High-elasticity liquid crystal elastomer fiber prepared based on a wet spinning method for adjusting viscosity and a preparation method thereof

CN117845356BActive Publication Date: 2026-10-16ZHEJIANG SCI-TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311851954.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-10-16
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

[0002]在过去的二十年中,熔融拉伸法、微流体法、直写式3D打印法、静电纺丝法等方法相继被开发出来用于制备纤维状的液晶弹性体,但这些方法都无法连续、高速制备高性能的人工肌肉微纤维

Benefits of technology

[0020] This invention successfully prepares highly elastic liquid crystal elastomer fibers using wet spinning. Compared with common methods, this invention has lower production costs and higher production efficiency, avoiding safety hazards under high temperature and high pressure conditions. Continuous and uniform fibers can be produced through needle spinning, and the nascent fibers are then stretched after passing through a coagulation bath. This process imparts certain mechanical properties and better elastic deformation capabilities to the fibers while avoiding unnecessary contamination. Ultimately, liquid crystal elastomer fibers with good recoverable elastic deformation are obtained. The method of this invention is simple to operate, requires minimal equipment, and is easy to promote and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117845356B_ABST
    Figure CN117845356B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high elasticity liquid crystal elastomer fiber based on the preparation of viscosity adjustment wet spinning method and a preparation method thereof.Belongs to the technical field of high-performance fiber preparation, and the method comprises the following steps: in the crosslinking process of liquid crystal elastomer, the viscosity of crosslinked polymer solution is continuously increasing, the spinning solution is regulated to a specific viscosity by component regulation and process control, the fiber is prepared by using the wet spinning process, and the surface of the fiber is further dried and removed by using a hot air blower when the fiber is pulled out from the coagulation bath, then the complete liquid crystal elastomer fiber is collected by drawing and winding.The spinning method is simple to operate and can be mass-produced, the prepared fiber has good continuity and uniform thickness, and the driving performance of the existing liquid crystal elastomer is broken through.The liquid crystal elastomer fiber obtained by the application has good mechanical properties, tensile properties and other characteristics, and can be applied in the fields of artificial muscle, intelligent fabric and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of liquid crystal elastomer fiber preparation, specifically relating to a high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method and its preparation method. Background Technology

[0002] Over the past two decades, methods such as melt stretching, microfluidics, direct-write 3D printing, and electrospinning have been developed for preparing fibrous liquid crystal elastomers. However, none of these methods can continuously and rapidly produce high-performance artificial muscle microfibers. Although we know that this material has many excellent properties, we have not been able to use it efficiently and at low cost to prepare artificial muscles. Therefore, this process remains in the laboratory stage and cannot be put into large-scale commercial production. Compared with common manufacturing technologies, wet spinning does not require excessively high extrusion temperatures and is also more environmentally friendly.

[0003] Wet spinning is a chemical fiber spinning method in which a polymer is dissolved in a solvent, spun into a fine stream through a spinneret, and then fed into a coagulation bath to form fibers. Fiber-forming polymers suitable for wet spinning have decomposition temperatures below their melting points or are prone to discoloration upon heating, and are soluble in suitable solvents. The solvent in the dopant stream diffuses into the coagulation bath, while the precipitant in the bath diffuses into the stream; this diffusion is called double diffusion. Through diffusion, the dopant stream reaches a critical concentration, and the polymer precipitates in the coagulation bath to form fibers. Coagulation is a physicochemical process, but some chemical fibers (such as viscose fibers) also undergo chemical changes during wet spinning.

[0004] The nascent fibers produced by wet spinning are in a swollen state due to the presence of a large amount of coagulation bath solution, resulting in highly mobile macromolecules and a very low degree of orientation. By selecting and controlling the spinning process conditions, fibers with different cross-sectional shapes or special capillary structures and properties can be obtained. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a high-elasticity liquid crystal elastomer smart fiber prepared by adjusting the viscosity of the spinning solution through wet spinning, and the same preparation method and apparatus. In view of the limitations of size and driving performance of the liquid crystal elastomer fibers prepared at present, the present invention abandons the common melt spinning and dry spinning technologies, and proposes a wet spinning viscosity control method to continuously prepare liquid crystal elastomer smart fibers with liquid crystal units oriented along the axial direction.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A highly elastic liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method includes the following steps:

[0008] (1) A certain amount of RM257 (2-methyl-1,4-phenyl 4-(3-acryloyloxypropoxy)benzoic acid), PETMPT (quaternary tetra-3-mercaptopropionic acid), EDDET (3,6-dioxa-1,8-octanedithiol) and catalyst were added to the spinning solution solvent and heated and stirred for 3-12 hours. The viscosity was controlled by changing the stirring time to change the crosslinking time, and the RM257 spinning solution with a viscosity between 250-350 mPa·s was obtained.

[0009] (2) Place the RM257 spinning solution on a wet spinning machine for wet spinning;

[0010] (3) A hot air blower is set after the coagulation bath in wet spinning. During wet spinning, the fiber is extruded from the spinneret and coagulated in the coagulation bath. The surface solution is further removed by the hot air blower to obtain a strand of fiber. The obtained fiber is stretched into a bundle and collected to obtain a high-elasticity liquid crystal elastomer fiber prepared by adjusting the solution in wet spinning.

[0011] In the above technical solution, further, in step (1), the concentration of RM257 in the RM257 spinning solution is 15wt%-30wt%, the concentration of EDDET is 0.5wt%-0.7wt%, the concentration of PETMPT is 0.1wt%-0.3wt%, and the concentration of catalyst is 0.1wt%-0.2wt%.

[0012] Furthermore, the spinning solution solvent is selected from one of the following: an aqueous solution of DMSO, an aqueous solution of DMAC, and an aqueous solution of DMF.

[0013] Furthermore, the spinning solution solvent is an aqueous solution of DMSO, and the mass ratio of RM257 to DMSO in the RM257 spinning solution in step (1) is 1:4.

[0014] Furthermore, during wet spinning, the spinneret speed is 2-8 mm / s, the receiving distance is 20 cm, and the receiving roller speed is 10 r / min.

[0015] Furthermore, the coagulation bath uses the same solvent as the spinning solution, with a concentration of 20wt%-50wt%, and the temperature of the coagulation bath is 20℃-60℃.

[0016] Furthermore, the stretching speed is 0.001-0.02 cm / sec, and the collection and winding speed is 0.001-0.02 cm / sec.

[0017] This invention prepares highly elastic liquid crystal elastomer smart fibers by adjusting the viscosity of the wet spinning solution. The process involves: during the crosslinking process of the liquid crystal elastomer, the viscosity of the crosslinked polymer solution continuously increases. A viscometer is used to test the viscosity of the spinning solution. By controlling its components and stirring time, the degree of crosslinking is controlled, thereby adjusting the viscosity of the spinning solution. The fibers are prepared using a wet spinning process. When the fibers are pulled out of the coagulation bath, a hot air blower is used to further dry and remove the surface coagulation bath residue. Subsequently, the fibers are drawn, wound, and collected to obtain complete liquid crystal elastomer fibers. The specific principle underlying this invention is that in the crosslinked network of the liquid crystal elastomer fiber, the distance between the liquid crystal molecules within the liquid crystal polymer with different degrees of crosslinking varies. If the liquid crystal macromolecules are arranged too tightly, the polymer viscosity is too high, resulting in poor flowability and hindering spinning. If the liquid crystal macromolecules are arranged too sparsely, the polymer viscosity is too low, and the spinning solution cannot form fibers. By selecting spinning solutions with different degrees of crosslinking through viscosity testing, this invention successfully achieves the wet spinning preparation of highly elastic liquid crystal elastomer fibers.

[0018] Furthermore, in the wet spinning process proposed in this invention for preparing liquid crystal elastomer fibers by controlling the viscosity of the spinning solution, as the spinning solution is extruded into the coagulation bath, the solvent in the spinning solution continuously exchanges with the water in the coagulation bath due to the concentration difference between the solvent in the spinning solution and the solvent in the coagulation bath. After hot air drying, complete liquid crystal elastomer fibers are obtained. By stretching, the initial orientation of the liquid crystal molecules is changed, guiding the extension of the flexible molecular chains and providing space for the rotation of the liquid crystal units, ultimately achieving the spontaneous orientation and alignment of the liquid crystal units. Finally, complete, highly elastic liquid crystal elastomer fibers are obtained.

[0019] The above technical solution has the following beneficial effects:

[0020] This invention successfully prepares highly elastic liquid crystal elastomer fibers using wet spinning. Compared with common methods, this invention has lower production costs and higher production efficiency, avoiding safety hazards under high temperature and high pressure conditions. Continuous and uniform fibers can be produced through needle spinning, and the nascent fibers are then stretched after passing through a coagulation bath. This process imparts certain mechanical properties and better elastic deformation capabilities to the fibers while avoiding unnecessary contamination. Ultimately, liquid crystal elastomer fibers with good recoverable elastic deformation are obtained. The method of this invention is simple to operate, requires minimal equipment, and is easy to promote and use. Attached Figure Description

[0021] The invention will be further described below with reference to the accompanying drawings:

[0022] Figure 1 A complete experimental apparatus diagram of a specific embodiment of the preparation device for implementing the method of the present invention (from left to right: extrusion pump, coagulation bath, hot air blower, stretching machine, collector).

[0023] Figure 2The spinning solutions are those of Example 5 (left) and Example 4 (right).

[0024] Figure 3 This is a comparison image of the fibers obtained in Example 10 before and after stretching.

[0025] Figure 4 The stress-strain curve of the fiber obtained in Example 10 under a single fiber tensile testing machine. Detailed Implementation

[0026] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments:

[0027] In the following examples, DPA (di-n-propylamine) was used as the catalyst. Unless otherwise specified, all reagents, materials, and equipment used were commercially available or prepared by conventional methods. Unless otherwise specified, all ratios are by mass.

[0028] Example 1

[0029] (1) RM257, PETMPT, EDDET and catalyst were dissolved in CH2Cl2 aqueous solution in sequence, heated to 40℃ and stirred for 3h, CH2Cl2:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5wt%, PETMPT 0.1wt%, and catalyst 0.1wt%;

[0030] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. The coagulation bath was a 30% concentration CH2Cl2 aqueous solution. During wet spinning, the diameter of the syringe spinneret was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 4 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 10 r / min.

[0031] Tests showed that CH2Cl2 and water would separate into layers. Although it could dissolve liquid crystal monomers well, it was not suitable as a coagulation bath and could not be used for double diffusion to remove the solvent, ultimately making wet spinning impossible.

[0032] Example 2

[0033] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 3h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0034] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. The coagulation bath was a 30% DMSO aqueous solution. During wet spinning, the diameter of the syringe nozzle was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 4 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 10 r / min.

[0035] Tests showed that the viscosity of the spinning solution was only 150 mPa·s. This viscosity is insufficient for the fiber forming process in the coagulation bath. The reason for this is that the stirring time of the spinning solution was too short, and the LCE monomers were not completely cross-linked into polymers, thus failing to form liquid crystal elastomer polymers.

[0036] Example 3

[0037] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 6h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0038] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. The coagulation bath was a 30% DMSO aqueous solution. The diameter of the syringe during wet spinning was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 4 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 10 r / min.

[0039] Tests showed that the viscosity of the spinning solution reached 200 mPa·s. This viscosity is unsuitable for fiber forming in the coagulation bath. The reason for this is that the stirring time of the spinning solution was too short, and the LCE monomers were not completely cross-linked into polymers, thus failing to form liquid crystal elastomer polymers.

[0040] Example 4

[0041] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0042] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. The coagulation bath was a 30% DMSO aqueous solution. The diameter of the syringe during wet spinning was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 4 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 10 r / min.

[0043] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30 wt%, and the temperature of the coagulation bath is 20℃.

[0044] Tests showed that the viscosity of the spinning solution reached 300 mPa·s. Spinning solutions with this viscosity are more likely to form fibers in the coagulation bath, resulting in fibers of uniform and continuous thickness.

[0045] Example 5

[0046] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 12h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0047] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 4 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 10 r / min.

[0048] Testing revealed that the spinning solution solidified directly. This viscosity of spinning solution precludes wet spinning experiments, indicating a problem: the fiber macromolecules underwent excessive cross-linking, resulting in solidification. Figure 2 In the middle, the left figure shows the spinning solution that solidified directly in this example, and the right figure shows the spinning solution with a certain viscosity in Example 4.

[0049] Example 6

[0050] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0051] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 6 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 20 r / min.

[0052] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30t, and the temperature of the coagulation bath is 20℃.

[0053] Tests showed that the experimentally produced liquid crystal elastomer fiber was pure white and possessed a certain degree of elasticity, with a maximum tensile strength of 250%.

[0054] Example 7

[0055] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, and catalyst 0.1 wt%;

[0056] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 8 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 30 r / min.

[0057] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30%, and the temperature of the coagulation bath is 20℃.

[0058] Tests showed that the experimentally produced liquid crystal elastomer fiber was pure white and possessed a certain degree of elasticity, with a maximum tensile strength of 350%.

[0059] Example 8

[0060] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0061] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.04 mm, the syringe size was 5 ml, the syringe advance speed was 10 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 40 r / min.

[0062] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30 wt%, and the temperature of the coagulation bath is 20℃.

[0063] Tests showed that the experimentally prepared liquid crystal elastomer fiber was pure white and possessed a certain degree of elasticity, with a maximum tensile strength of 300%. This represents a decrease compared to Example 7.

[0064] Example 9

[0065] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO aqueous solution in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5 wt%, PETMPT 0.1 wt%, catalyst 0.1 wt%;

[0066] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.08 mm, the syringe size was 5 ml, the syringe advance speed was 10 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 40 r / min.

[0067] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30 wt%, and the temperature of the coagulation bath is 20℃.

[0068] Tests showed that the experimentally produced liquid crystal elastomer fiber was pure white and possessed a certain degree of elasticity, with a maximum tensile strength of 400%.

[0069] Example 10

[0070] (1) RM257, PETMPT, EDDET and catalyst were dissolved in DMSO in sequence, heated to 40℃ and stirred for 9h, DMSO:RM257=4:1, to obtain a 20wt% RM257 solution, in which the mass concentrations of each component are: RM257 20wt%, EDDET 0.5wt%, PETMPT 0.1wt%, and catalyst 0.1wt%;

[0071] (2) The prepared RM257 solution was placed in a disposable syringe and then placed on a wet spinning machine for wet spinning. During wet spinning, the needle diameter was 0.06 mm, the syringe size was 5 ml, the syringe advance speed was 10 mm / s, the receiving distance was 20 cm, and the receiving roller speed was 40 r / min.

[0072] (3) The obtained liquid crystal elastomer fibers are subjected to stretching treatment. The stretching speed is 0.001-0.02 cm / sec, the collection and winding speed is 0.001-0.02 cm / sec, the concentration of the coagulation bath is 30 wt%, and the temperature of the coagulation bath is 20℃.

[0073] Tests showed that the experimentally produced liquid crystal elastomer fiber was pure white and possessed a certain degree of elasticity, with a maximum tensile strength of 480%.

[0074] Figure 3 The images show a comparison of the fibers obtained in this example before and after stretching. The top image shows the natural length of the fibers under static conditions, while the bottom image shows the curve length after manual stretching. Figure 4 The stress-strain curve of the fiber obtained in this example under a single fiber tensile testing machine shows that the fiber's dynamic tensile strength can reach a maximum deformation of 480%, indicating high elasticity.

Claims

1. A highly elastic liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method, characterized in that: Its preparation method includes the following steps: (1) RM257 (2-methyl-1,4-phenyl 4-(3-acryloyloxypropoxy)benzoic acid), PETMPT (quaternary tetra-3-mercaptopropionic acid ester), EDDET (3,6-dioxa-1,8-octanedithiol) and catalyst were added to the spinning solution solvent and heated and stirred for 3-12 hours. The viscosity was controlled by changing the stirring time to change the crosslinking time, and the viscosity of the RM257 spinning solution was obtained, which was between 250-350 mPa·s. The spinning solution solvent was an aqueous solution of DMSO. (2) The RM257 spinning solution is placed on a wet spinning machine for wet spinning; during wet spinning, the nascent fiber is obtained by extruding the spinneret through the coagulation action of the coagulation bath; the coagulation bath is the same solvent as the spinning solution. (3) A hot air blower is set up after the coagulation bath of wet spinning. The surface solution is further removed by the hot air blower to obtain a strand of fiber. The obtained fiber is stretched into a bundle and collected to obtain a high elastic liquid crystal elastomer fiber prepared by adjusting the solution based on wet spinning.

2. The high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method according to claim 1, characterized in that, In step (1), the concentration of RM257 in the spinning solution is 15wt%-30wt%, the concentration of EDDET is 0.5wt%-0.7wt%, the concentration of PETMPT is 0.1wt%-0.3wt%, and the concentration of catalyst is 0.1wt%-0.2wt%.

3. The high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method according to claim 1, characterized in that, Step (1) The mass ratio of RM257 to DMSO in the RM257 spinning solution is 1:

4.

4. The high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method according to claim 1, characterized in that, During wet spinning, the spinneret speed is 2-8 mm / s, the receiving distance is 20 cm, and the receiving roller speed is 10 r / min.

5. The high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method according to claim 1, characterized in that, The concentration of the coagulation bath is 20wt%-50wt%, and the temperature of the coagulation bath is 20℃-60℃.

6. The high-elasticity liquid crystal elastomer fiber prepared by adjusting viscosity using a wet spinning method according to claim 1, characterized in that, The stretching speed is 0.001-0.02 cm / sec, and the collection and winding speed is 0.001-0.02 cm / sec.

Citation Information

Patent Citations

  • Preparation method and device of single-domain liquid crystal elastomer intelligent fiber

    CN114381823A